If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 + 19c = 50 + -6c Solving 100 + 19c = 50 + -6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6c' to each side of the equation. 100 + 19c + 6c = 50 + -6c + 6c Combine like terms: 19c + 6c = 25c 100 + 25c = 50 + -6c + 6c Combine like terms: -6c + 6c = 0 100 + 25c = 50 + 0 100 + 25c = 50 Add '-100' to each side of the equation. 100 + -100 + 25c = 50 + -100 Combine like terms: 100 + -100 = 0 0 + 25c = 50 + -100 25c = 50 + -100 Combine like terms: 50 + -100 = -50 25c = -50 Divide each side by '25'. c = -2 Simplifying c = -2
| 29h+41= | | (2y-1)=180 | | y=3ab(-2a+b)2 | | 2(x-3)2+7=23 | | (-i)-(5+(7*i))+4= | | (4y+16)=180 | | 8t+6=30+2t | | (1-i)x-1=i | | 2t-1=3[t+3] | | 2/4=p/8 | | 4(3x+2)+1=21 | | 15t+30=67 | | v-1/2=21/20 | | 3(b+4)+b=3(b-3)-2 | | 6x=1x+16 | | 36-1m-48=0 | | (2+i)x+5-i=3i | | 500=45t | | 42+36L-6L^2=94.5 | | 2x-10y= | | 4(-3y+2)-16x=0 | | -3x(x-8)+7x=12 | | x-10/3=5 | | 42+36L-6L^2=96 | | 4(7x-34)=88 | | 70=120-3x | | 80=-10n-10 | | 3x-13-5x+2=21-2x-2-5x | | x+0.5x=60000 | | 3(3x+9)+7=9x+34 | | 5x/6-1/2=5x/12 | | 1x+3x+1= |